Integrative and complementary practices: a strategy for the Promotion of women's health (Research, Society and Development, 2021)
For having specificities arising from their gender and sex condition, the female population demands an assistance that is less and less interventionist, medicated, and disease-centered. Therefore, the objective of this study was to analyze the use of Integrative and Complementary Practices (ICPs) as a strategy to promote Women's Health, verifying the most used PICs, the context of women's lives in which they are applied, and what benefits they bring to this public. This study is an integrative literature review developed in the following databases: LILACS, MEDLINE and BDENF, using Boolean operators combined with health descriptors from DeCS in the following combinations: "Complementary Therapies" AND "Women's Health"; "Integrative Medicine" AND "Women's Health"; "Traditional Medicine" AND "Women's Health" and by the name of each PIC currently in SUS AND "Women's Health". The final sample was composed of 16 articles, 10 from MEDLINE and 6 from LILACS. The studies addressed the use of therapies such as music therapy, acupuncture and its techniques, yoga, guided relaxation, hydrotherapy, and breathing techniques, among others. The PICs were applied to women experiencing pregnancy, labor, SOP, work, smoking, cancer, climacteric and elderly. Alternative therapies proved to be a viable option in the treatment and promotion of health, acting as a complement to conventional medicine.